Clinical impact of MEFV mutations in children with periodic fever in a prevalent western European Caucasian population. Issue 12 (12th May 2012) - Federici, Silvia; Calcagno, Giuseppina; Finetti, Martina; Gallizzi, Romina; Meini, Antonella; Vitale, Agata; Caroli, Francesco; Cattalini, Marco; Caorsi, Roberta; Zulian, Francesco; Tommasini, Alberto; Insalaco, Antonella; et al.
Abstract : Objective: To evaluate the actual impact of MEFV mutations on clinical manifestations associated with fever attacks in Caucasian children with periodic fever. Methods: 113 children carrying MEFV mutations (44 with mutations in two alleles, 69 heterozygous) and 205 children negative for mutations in genes associated with periodic fevers were analysed. The following groups of patients were considered: patients carrying two high penetrance mutations (M694V, M694I, M680I); one high, one low penetrance mutation; two low penetrance mutations; one high penetrance mutation; one low penetrance mutation; genetically negative patients. Results: Patients with two MEFV mutations displayed a shorter duration of fever attacks and higher prevalence of a positive family history than patients carrying one MEFV mutation and genetically negative patients. Severe abdominal pain, chest pain and pleurisy were also more frequent in patients with two MEFV mutations compared with children with one MEFV mutation and genetically negative patients. Conversely, a higher frequency of exudative and erythematous pharyngitis, enlargement of cervical lymph nodes, aphthous stomatitis and non-specific skin rash was observed in genetically negative patients and, to a lesser extent, in patients with one MEFV mutation. The frequency of 'familial Mediterranean fever (FMF)-like symptoms' decreases from patients carrying two high penetrance mutations towards patients with a single low penetrance mutation with an opposite trend for 'periodic fever, aphthous stomatitis, pharyngitis, adenitis-like symptoms'. Conclusions: This clinical observation supports recent findings contrasting the notion of FMF being a pure autosomal recessive disorder associated with recurrence of mutations leading to loss of protein function. A dosage effect could be invoked, giving rise to symptom onset even in the presence of one wild-type allele.